Clinical Ophthalmic Oncology 2014
DOI: 10.1007/978-3-642-54255-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathology of Uveal Melanoma

Abstract: Like other cancers, uveal melanomas (UM) are characterised by an uncontrolled, clonal, cellular proliferation, occurring as a result of numerous genetic, and epigenetic aberrations. Signalling pathways known to be disrupted in UM include: (1) the retinoblastoma pathway, probably as a result of cyclin D1 overexpression; p53 signalling, possibly as a consequence of MDM2 overexpression; and the P13K/AKT and mitogen-activated protein kinase/extracellular signal-related kinase pathway pathways that are disturbed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 125 publications
2
15
0
Order By: Relevance
“…This result again differs from the current study, in which only a single case demonstrated polysomy 8q. Although the frequency of monosomy 3 and polysomy 8q detected in IM in our cohort is lower (15% and 6%, respectively) than that described in the two above-mentioned papers, it is consistent with that of genetic alterations commonly reported in choroidal melanomas 12 17–19. It is possible that the differing frequencies of chromosomal alterations observed in IM reflect varying genetic analytical techniques used in the studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This result again differs from the current study, in which only a single case demonstrated polysomy 8q. Although the frequency of monosomy 3 and polysomy 8q detected in IM in our cohort is lower (15% and 6%, respectively) than that described in the two above-mentioned papers, it is consistent with that of genetic alterations commonly reported in choroidal melanomas 12 17–19. It is possible that the differing frequencies of chromosomal alterations observed in IM reflect varying genetic analytical techniques used in the studies.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, most (if not all) studies have not found BRAF mutations in either primary or metastatic posterior UM 12. Intriguingly, however, Henriquez et al 27 reported T1799A mutations in the BRAF gene in 9/19 (47%) cases of IM.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[4][5][6] originally, loss of one chromosome 3 was identified as an important marker of poor prognosis, and this has been substantiated in many studies. However, later studies have also identified the importance of other chromosomes: gain of chromosome 8q is also correlated with death due to metastases, [5][6][7][8][9][10][11][12][13][14] while an extra chromosome 6p is associated with a better survival. 8 10 15-18 In separate studies, gene expression profiling has also been identified as a reliable method for prognostication.…”
Section: Introductionmentioning
confidence: 99%
“…However, increased apoptosis could only be found in combination with a PI3K inhibitor, leading to reduced AKT activity [50,51]. Indeed, MEK inhibitors also inhibit the proliferation of uveal melanoma cells, in a mutant GNAQ/GNA11-dependent manner.…”
Section: Targeting Kinasesmentioning
confidence: 99%